Fish Dryer With Temperature Control Using the Fuzzy Logic Method - Raja Muradi; Kartika Kartika (Master Program of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2023)
Fish is a food in great demand at home and abroad, and apart from its delicious taste, fish is also prevalent because of its health benefits. High protein content and lower fat content compared to other animal protein sources. However, the quality of fish is effortless to decline and spoil. One of the efforts to preserve processed fish so that it can be stored for a more extended period is using preservation. The purpose of preserving fish is to keep fish as long as possible by eliminating the causes of spoilage. There are various types of fish preservation, one of which is drying. Fish drying is a process of reducing the water content in fish to inhibit spoilage. Several factors affect the drying fish’s operation: temperature and airflow velocity. Temperatures that are too large can cause case hardening where the outside of the fish is dry, but the inside is still wet. Then the temperature chosen in this study was 50°C and 60°C with consideration of nutritional standards for dried fish and airflow velocity of 1.5 - 2 m/s. According to SNI 2732.3: 2009, the maximum water content in dried fish is 40%. This system is supported by a type k thermocouple temperature sensor, load cell sensor, tubular heater, fan, solid state relay, keypad, I2C LCD, and Arduino mega. Two input variables must be controlled in a fish dryer: temperature and weight. At variable temperatures, the input is a type k thermocouple sensor. The output is an SSR that holds the tube heater so that the temperature of the fish dryer matches the setpoint temperature. The fuzzy logic method controls the temperature when drying fish does not exceed the set point temperature.